The use of ballistic trajectory and granular flow models in predicting rockfall propagation. Issue 4 (16th January 2013) - Bourrier, Franck; Dorren, Luuk; Hungr, Oldrich
ABSTRACT: The term rockfall is often used ambiguously to describe various mass movement processes. Here we propose more precise terminology based on the physical nature of the moving mass, differentiating between two distinct types of rockfall: fragmental rockfall and rock mass fall. For both rockfall types, the current knowledge of the mechanisms controlling propagation of the mass movement are described, showing how these mechanisms can be simulated with different modelling approaches. However, we point out that almost no development has been realized concerning dynamic behaviour of the transitional processes between these two end‐member rockfall types. Some simplified means of dealing with these complications are suggested, but we emphasize that a considerable amount of fundamental methodological development remains necessary. Copyright © 2012 John Wiley & Sons, Ltd.